Pemanfaatan Teknologi Tepat Guna Mesin Pemarut Kelapa Untuk IKM. Wingko Babat Cap Pohon Kelapa - Syakhroni, Akhmad; Khoiriyah, Nuzuia; Ulin Adira P (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
Wingko Babat Cap Pohon Kelapa is a micro business that is already 6 years old. This wingko is still produced traditionally and today. Since improvements were made to the wingko packaging design, the demand for Coconut Tree wingko stamp sold in stores by Semarang City has increased. But the obstacle faced by owners is the speed in meeting consumer demand. The problem experienced is an obstacle in the process of doing coconut shredding. The coconut shredding process carried out independently by SMIs is not carried out in shredding services such as those in the market, because SMIs want to ensure that the process carried out is clean and hygienic. The current machine is an old machine with a capacity of 3 kg / 30 minutes and must be carried out a 2x shredding process in order to get good results, thus making the production process run longer. The scar tool owned by IKM is currently very simple and less safe in use because it does not have a scar safety standard. SMIs need to carry out the process of repairing production equipment in order to increase production speed and capacity to meet customer demand and also to improve user safety. Procurement of tools needs to be done so that SMEs are able to increase their productivity, work safety and security.